Congenital heart diseases: A review of echocardiogram records (KYAMC Journal, 2018)
Congenital heart defect (CHD) means an anatomic malformation of the heart or great vessels which occurs during intrauterine development, irrespective of the age at presentation. They can disrupt the normal blood flow through the heart. The blood flow can slow down, go in the wrong direction or to the wrong place, or be blocked completely. Broadly congenital heart defects can be acyanotic and cyanotic. We have reviewed retrospectively from echocardiogram record nearly two years of period & collected total 404 patients with congenital heart defects. Among them 329 (81.43%) was acyanotic and 75 (18.57%) was cyanotic congenital defects with variety of diagnosis. Ventricular septal defect was the most common acyanotic heart defect and Tetralogy of Fallot was the most common cyanotic heart defect. There was no significant gender deference.KYAMC Journal Vol. 9, No.-1, April 2018, Page 35-38